Mapping the Impossible : Incongruent Transposition as a Method of Playing - Hernandez, Katt (2018)
This is a two-part presentation of a non-traditional transposition and improvisation technique, first demonstrating the transposition practice itself, as I have developed it to date, then demonstrating how I have employed it both in research and in teaching. Transposition of non-musical sources, especially field recordings and incongruent real world sounds from a variety of environments, is a part of my artistic practice which is rooted in both improvisation and electroacoustic composition. I have also used it extensively in the teaching of both improvisation and composition for many years, both in Sweden and the U.S. The most basic version of this practice is to procure recordings of real world sounds, or physically play in environments such as in parks or industrial basements, on shipping docks, roadways or street corners, under bridges and so on, “transposing” the sounds of those places, in the somewhat the same way one would transpose a solo or tune from a record. This way of playing yields new ways of approaching both the instrument at hand and the production of sound on a more general level. Utilizing this method offers questions about the differences between imitation and allegory. and helps the player(s) to explore the territory between the concrete and the imagined, affording the opportunity to experience the interplay between the source and the artifacts or extrapolations that come from the impossible attempt to “play” it. It can be explored on a spectrum ranging from the most intuitive sort of playing to the most meticulous sort of re-construction and analysis, and applied in musical practices ranging from the entirely spontaneous to the carefully composed. It is also a method for learning to listen to sound-generating sources other than humans. Most sounds one finds in the inanimate or even animal environment cannot or do not react in the way another musician would, nor even offer the familiar cues for listening and processing information while playing found on a recording of music. These sounds are, in a way, defenseless, and thus demand attention to afford their sonic details to a would-be learner of their ways This playing-based method dwells outside the types most often found in higher education contexts. It is part of my practice in improvisation, a field that only exists in its own right at a fraction of music institutions. It is cousin to a broader of an array of idiosyncratic methods which, while a mainstay of alternative and underground music scenes the world over, have had little true entry into institutions of higher learning. Yet the lion’s share of development and teaching in these improvised music genres is based entirely on playing. By turning outwards from the environment of higher education to visceral methods such as these, new materials are brought back inwards for use and consideration by researchers, instructors and students. It is one of many possible examples of coming upon and disseminating methods not otherwise available to musicians pursuing work in improvisational practices and techniques in a higher education environment.
Keywords: transposition; violin; field recording; psychogeography